Challenges and Benefits of Facilitating Online Learning in Time of Covid-19 Pandemic: Insights and Experiences of Social Science Teachers - Junsay Jr., Feddy B.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
Online education is a rapidly growing phenomenon for teachers. With the outbreak of COVID-19, there are changes in all societies worldwide, and a forcible shift in the medium of teaching and learning is inevitable. This paper explored the social science teachers' lived experiences in a Chinese school during the COVID-19 Pandemic. This qualitative study utilized the phenomenological approach to explore the lived experiences of eight full-time and tenured social science teachers determined using purposive sampling. The data were collected from the participants using an in-depth semi-structured interview. Meanwhile, the recursive textual analysis guided by the three C's of Lichtman was employed to analyze the data thematically. The findings show that social science teachers faced challenges in online teaching such as personal, technical, and teaching strategies. It also found that the teachers have difficulty motivating students to participate in the online class activities and submission of outputs. Despite the challenges, the teachers were able to surmount the difficulties because of the support of the administration and their fellow teachers. Generally, the unfolding of online teaching challenges confronted by school heads, teachers, and students will make them resilient to adapt and embrace virtual education. Keywords. Social Science, online education, COVID-19 Pandemic, phenomenology, Philippines